Combination of Mobile Infrastructure Based Routing Protocol and RSU-Advertisement Routing Protocol in Urban VANET - Gunawan, Dedi; Nugroho, Yusuf Sulistyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Vehicular ad hoc network (VANET) is a subclass of mobile ad hoc network (MANET), in which it is used to support intelligent transportation system. Generally, the main problem in VANET is in routing protocol. This is a challenging task due to the fact that moving object with certain direction and speed always changes the network topology quickly. Some routing protocols actually have been proposed to deal with routing complexity. In this paper we proposed new approach which was combining the existing routing protocol in order to reduce the dropping package in dynamic environment. By combining mobile infrastructure base routing (MIBR) and advertisement routing, the packet loss could be reduced. MIBR used certain type of vehicle on the road as the priority of routing hop. While, placing fixed wireless infrastructure in the roadside (RSU) would be helpful in case of traffic jam, since it could forward the package to the most far targeted vehicle when other vehicle hop experiences stuck.